Pengaruh Tingkat Pendidikan Dan Pelatihan Terhadap Kompetensi Lulusan Peserta Pada Lembaga Pelatihan Kerja (LPK) PT. Satria Tamtama Rahayu - Ira Pebrianti Syamhadi; Nelly Martini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to know, analyse, and explain: The extent of the relationship between education level and training on competency of participants graduates. Partial influence between the level of education and training on the competence of graduates of participants. Simultaneous influence between the level of education and training on the competence of graduates of participants. Data collection techniques using questionnaire and literature. The population in this research is a participant who graduated at PT Satria Tamtama Rahayu and has been placed in the industrial company with samples used as many as 135 respondent. Data obtained from respondents was processed using test aids using IBM SPSS 22. The results showed that:) There was an influence on the level of education on the competency of participant graduates. There is no training influence on the competency of participant graduates. There are influences on the level of education and training on the competency of participant graduates. The value of coefficient of determination (R2) amounted to 0,662 or66,2% which means that 66,2% of participants graduates competencies are influenced by education and training levels, while the remaining 33,8% are influenced by other variables not examined in this study. Keywords: Competency Graduates participants, education level, training.